2014
DOI: 10.1021/ar4001839
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Access to α-Oxo Gold Carbenes by N–O Bond Oxidants

Abstract: Metal carbenes are highly versatile species that mediate various transformations. Recent advances in gold catalysis have allowed catalytic access to α-oxo metal carbenes from the alkyne functionality. Compared with traditional methods that rely upon metal-catalyzed decomposition of diazo precursors, the generation of this synthon occurs in an environmentally more appealing fashion by gold-catalyzed alkyne oxygenation. Hydroxylamine derivatives are typically prepared from hydroxylamine salts that are cheap and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
70
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(74 citation statements)
references
References 70 publications
(67 reference statements)
1
70
0
3
Order By: Relevance
“…The Au-catalyzed Noxide assisted alkyne oxidation and cycloisomerization of 1,nenynes are particularly notable gold-carbene-based transformations. [2, 3] In addition, the nucleophilic nitrenoid equivalents, for example, azides, [4] pyridium ylides, [5] 2H-azirines, [6] and others [7] have been used in the generationo fg old carbene species. The formation of Au-carbenes from ynamides occurs via the elimination of ac ounter ion or al eaving group after electron back donation of gold (Scheme 1a).…”
mentioning
confidence: 99%
“…The Au-catalyzed Noxide assisted alkyne oxidation and cycloisomerization of 1,nenynes are particularly notable gold-carbene-based transformations. [2, 3] In addition, the nucleophilic nitrenoid equivalents, for example, azides, [4] pyridium ylides, [5] 2H-azirines, [6] and others [7] have been used in the generationo fg old carbene species. The formation of Au-carbenes from ynamides occurs via the elimination of ac ounter ion or al eaving group after electron back donation of gold (Scheme 1a).…”
mentioning
confidence: 99%
“…(1)].I ndeed, the reaction of ynamides 1a with enantio-enriched (S)-2g (200 mol %) in the presence of HNTf 2 catalyst led to isolation of 3a in excellent yield (94 %) and good enantioselectivity (83 %ee), providing ad irect proof that concerted S N 2' pathway is operative. (1)]. [18] We quickly applied this test to typical Au [5a] and Zncatalyzed conditions, [5c] again leading to asignificant enantioinduction in both cases [66-82 % ee,E q.…”
mentioning
confidence: 99%
“…[10b,11] Regardless of which resonance form is the predominant one,the carbon atom bound to gold is electron-deficient, and the gold carbene shows electrophilicity akin to Fischer carbenes. [10][11][12] Enamides are active nucleophiles that are also capable of participating in aza-ene reactions with imines. [10][11][12] Enamides are active nucleophiles that are also capable of participating in aza-ene reactions with imines.…”
mentioning
confidence: 99%
“…In the presence of 10 mol %o fL1AuNTf 2 ,avariety of chiral phosphoric acids [17] were surveyed in the reaction of diazoacetate 1a and enamide 2a (Table 1, entries 1-4). Surprisingly,l owering the amount of chiral phosphoric acid 5d led to as ignificant improvement in the enantioselectivity while the yield was maintained (entries [12][13][14][15]. As olvent screen showed that the use of methyl tert-butyl ether (MTBE) enhanced the enantioselectivity of this process (entry 5; see also the Supporting Information, Table S1).…”
mentioning
confidence: 99%